2019
DOI: 10.1111/nuf.12408
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a MEWS‐Sepsis screening tool: Transformational outcomes of a nurse‐led evidence‐based practice project

Abstract: Background: One in three patients who die in the hospital has sepsis. Alerting clinicians to early detection of high-risk patients before deterioration is a top health care priority. Modified Early Warning Scoring (MEWS) tools have assisted organizations in identifying at-risk patients at the first sign of subtle deterioration.Aim and setting: In conjunction with an academic-clinical partner, we evaluated, revised and implemented a modified MEWS-Sepsis screening tool in an acute care facility.Participants: One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…Sepsis protocols. Eight of the selected studies examined the effectiveness of sepsis protocols [24,[36][37][38] and sepsis screening tools [16,[39][40][41] for the early assessment and management of sepsis (Table 7). All of these articles revealed that the implementation of sepsis screening tools or protocols based on the SSC guidelines leads to the early identification and timely management of sepsis, as well as the improvement in nurses' compliance to the SSC guidelines for the detection and management of sepsis.…”
Section: Interventions Directed At Improving Nurses' Sepsis Assessmen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis protocols. Eight of the selected studies examined the effectiveness of sepsis protocols [24,[36][37][38] and sepsis screening tools [16,[39][40][41] for the early assessment and management of sepsis (Table 7). All of these articles revealed that the implementation of sepsis screening tools or protocols based on the SSC guidelines leads to the early identification and timely management of sepsis, as well as the improvement in nurses' compliance to the SSC guidelines for the detection and management of sepsis.…”
Section: Interventions Directed At Improving Nurses' Sepsis Assessmen...mentioning
confidence: 99%
“…tested to examine their impact on some patient outcomes, and variabilities were identified. For example, the use of the Modified Early Warning Score (MEW-S) tool revealed no significant improvement in patient mortality rate [41]. In contrast, mortality rates were decreased by using the Nurse Driven Sepsis Protocol (NDS) [40], Quality Improvement (QI) initiative [38], and a computerized protocol [37].…”
Section: Plos Onementioning
confidence: 99%
“…In this sense, the nursing team has a fundamental role, as patient monitoring is predominantly performed by these professionals. Nurses remain at the bedside for much longer and often recognise the patient with sepsis early, facilitating the beginning of treatment and favouring a positive outcome (Rhodes et al, 2017; Roney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses remain at the bedside for much longer and often recognise the patient with sepsis early, facilitating the beginning of treatment and favouring a positive outcome (Rhodes et al, 2017;Roney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research supports the integration of EBP to enhance quality of health care, improve health outcomes, reduce variations in care and decrease costs (Melnyk et al, 2012;Pravikoff et al, 2005;Spies et al, 2018). The integration of evidence-based interventions in nursing care can greatly improve patient outcomes such as decreasing hospital-acquired pressure ulcers and reduction of sepsis-related clinical concerns (Barakat-Johnson et al, 2020;Jacobs, 2020;Roney et al, 2020). Students need to see the incorporation of EBP as a way to address any decision in patient care rather than something extra to do.…”
Section: Introductionmentioning
confidence: 99%